Biomarker evidence of a serpentinite chemosynthetic biosphere at the Mariana forearc - Palash Kumawat; Elmar Albers; Wolfgang Bach; Frieder Klein; Walter Menapace; Christoph Vogt; Florence Schubotz (Communications Earth & Environment)
Abstract Present-day serpentinization systems, such as that at the Mariana forearc, are prominent sources of reduced volatiles, including molecular hydrogen (H2) and methane (CH4), and are considered analogs for chemosynthetic ecosystems on early Earth. However, seepage of serpentinization fluids through mud volcanoes at the Mariana forearc seafloor is defined by high pH, and nutrient scarcity, creating challenging conditions for microbial life. We present geochemical and lipid biomarker evidence for a subsurface biosphere shaped by episodic substrate availability, highlighting microbial persistence across steep geochemical gradients within serpentinite mud. Light stable carbon isotope compositions from diagnostic lipids reveal a temporal shift from hydrogenotrophic methanogenesis to sulfate-dependent anaerobic methane oxidation. Membrane adaptations, including unsaturated diether, acyclic and branched tetraether, and ether-based isoprenoidal and non-isoprenoidal glycosidic lipids, reflect microbial strategies for coping with this extreme environment. Our findings establish the Mariana forearc as a unique serpentinite-hosted biosphere, where life operates at the fringes of habitability.